The new Berlin : memory, politics, place - Till, Karen E. (University of Minnesota Press, 2005)
Four locations frame The New Berlin: the Topography of Terror, the Memorial to the Murdered Jews of Europe, the Jewish Museum, and Sachsenhausen Concentration Camp Memorial and Museum. Through field notes, interviews, archival texts, personal narratives, public art, maps, images, and other sources, Karen Till describes how these places and spaces exemplify the contradictions and tensions of social memory and national identity.